PENGARUH POLIMER PC DENGAN ADDITIF TWEEN-80 TERHADAP KARAKTERISTIK POLIMER DAN RECOVERY FACTOR PADA MINYAK 39 °API DI BATUAN SANDSTONE - Tilano, Adrian; Samsol; Fattahanisa, Aqlyna (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2024)
Background: The increasing demand for petroleum and the depletion of oil reserves in oil fields require the development of more efficient oil recovery techniques to enhance oil production. One method that can be employed is Enhanced Oil Recovery (EOR), where chemical injection becomes a viable approach. One chemical injection method that can be used is polymer injection. One suitable polymer for this purpose is cellulose polymer (PC). Cellulose polymer (PC) is the most abundant polymer in nature, a renewable material that is degradable, biocompatible, cost-effective, and non-toxic. Cellulose can be derived from plants and certain types of bacteria.Objective: This research aims to investigate the influence of temperature variations on cellulose polymer (PC) with Tween-80 additive on the Recovery Factor.Methodology: Laboratory experiments were conducted using the core flooding technique with a core holder, applying the slug method with various °API variations on light crude oil with an API gravity value of 39. Sandstone rock samples were used in the experiments, prepared by saturating with brine and oil.Result: The laboratory results showed a recovery percentage of 7.89% at a temperature of 60 °C and 17.86% at a temperature of 80 °C. The highest increase in oil recovery was observed at a temperature of 80 °C, with a recovery factor of 17.86%. In conclusion:, based on the conducted core flooding experiments, the best recovery factor was found in polymer injection using PC with Tween-80 additive at a temperature of 80 °C.